Thermal decomposition and combustion analysis of Malaysian peat soil samples using Coats Redfern model-free method - Musa, Dayang Nur Sakinah; Jamil, Hamidah; Mohd Tohir, Mohd Zahirasri; Syam, Syafiie; Yahaya, Ridwan (Universiti Putra Malaysia, 2024)
This research investigates the thermal decomposition behaviour of Malaysian peat soil through thermogravimetric analysis at varying heating rates. The study aims to analyse the thermal kinetics of decomposition for distinct peat soil types under inert and oxidative atmospheres while considering the role of available oxygen. The investigation encompasses virgin and agricultural peat, employing a non-isothermal thermogravimetric analysis technique to evaluate thermal decomposition characteristics and compute kinetic parameters using the Coats Redfern model-free approach. The pyrolysis profiles reveal three primary stages: moisture evaporation (30–180°C), organic component decomposition (200–500°C), and mineral decomposition (600–800°C). Virgin peat experiences a 43% mass loss during pyrolysis, while agricultural peat shows a 46% mass loss, emphasising insights into thermal behaviour and consistent decomposition patterns across peat types. Combustion profiles exhibit three main stages: dehydration (30–180°C), oxidative pyrolysis transforming organic matter into volatiles and char (200–300°C), and subsequent char oxidation (300–500°C). The study determines average activation energy trends, measuring 14.87 kJ/mol for virgin peat and 5.37 kJ/mol for agricultural peat under an inert atmosphere, and 28.89 kJ/mol for virgin peat and 36.66 kJ/mol for agricultural peat under an oxidative atmosphere. The research introduces an innovative two-step reaction model elucidating peat thermal decomposition kinetics (excluding dehydration), including a discussion on the impact of oxygen availability on kinetic parameters. These findings essential peat fire smouldering modelling, contributing to peat combustion behaviour for effective strategies to reduce peat fire risks.